Hypertension in the Elderly - Blas Gil-Extremera; Pedro Cía-Gómez (International Journal of Hypertension)
Background. The incidence of hypertension in the Western countries is continuously increasing in the elderly population and remains the leading cause of cardiovascular and morbidity. Methods. we analysed some significant clinical trials in order to present the relevant findings on those hypertensive population. Results. Several studies (SYST-EUR, HYVET, CONVINCE, VALUE, etc.) have demonstrated the benefits of treatment (nitrendipine, hydrochrotiazyde, perindopril, indapamide, verapamil, or valsartan) in aged hypertensive patients not only concerning blood pressure values but also the other important risk factors. Conclusion. Hypertension is the most prevalent cardiovascular disorder in the Western countries, and the relevance of receiving pharmacological treatment of hypertension in aged patients is crucial; in addition, the results suggest that combination therapy—nitrendipine plus enalapril—could have more benefits than those observed with the use of nitrendipine alone.